The Relationship of Job Stress and Job Satisfaction with Organizational Commitment in Environmental and Occupational Health Staff Working in Alborz and Ahvaz Jundishapur Universities of Medical Sciences - Amin Torabipour; Seyed Mehdi Emamyanfard; Mohammad Veysi Sheykhrobat; Maghsoud Jafarinia (پژوهش‌های سلامت‌محور, 2019)
The Relationship of Job Stress and Job Satisfaction with Organizational Commitment in Environmental and Occupational Health Staff Working in Alborz and Ahvaz Jundishapur Universities of Medical Sciences